Development of Local Food Products in Rejang Lebong According to Islamic Economics - Hendrianto Hendrianto; Noza Aflisia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to explore more deeply the strategies for obtaining raw materials, diversification, and marketing of local food products of Rejang Lebong and the ethics according to Islamic economics. This qualitative descriptive study used data collection techniques in the form of observation, interviews, and documentation. Meanwhile, the data processing and analysis techniques used were descriptive and analytic. The results showed that the strategy for obtaining raw materials for local food production was by selecting quality raw materials. Diversification of local food products of several forms, namely Jantan Cookies, Vegetable Chips, and Krispi Petai. Marketing of local food products of Rejang Lebong is carried out by consignment, Direct Selling, Open Reseller, Online Shopping Applications such as Blanja.com, Shopee, Bukalapak, Tokopedia, social media such as Facebook, Instagram, Twitter, Youtube, Website, Whatsapp, and Television. Meanwhile, ethics in the development of local food products of Rejang Lebong according to the Islamic economic perspective, namely being honest, accepting criticism and suggestions from consumers, beneficial for others, affordable prices, not vilifying other people's businesses, not hoarding goods, not monopolizing, not selling haram goods, free from the element of Riba, and without coercion.